2012
DOI: 10.1016/j.rmed.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A better response in exercise capacity after pulmonary rehabilitation in more severe COPD patients

Abstract: Single variables from lung function or exercise testing at baseline have limited predictive value for response to exercise training. However, patients with worse disease status (i.e. a combination of lower FEV(1), more hyperinflation, lower exercise capacity and worse quadriceps force) improve more in endurance exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 35 publications
4
36
2
Order By: Relevance
“…Similar evidence has been reported in patients with COPD [24,31,32] . As well as for patients with COPD, it is conceivable that even patients with non-CF bronchiectasis and a poor baseline lung function are at risk of entering a downward spiral of dyspnea, sedentariness, demotivation, and, finally, deconditioning [33] .…”
Section: Discussionsupporting
confidence: 87%
“…Similar evidence has been reported in patients with COPD [24,31,32] . As well as for patients with COPD, it is conceivable that even patients with non-CF bronchiectasis and a poor baseline lung function are at risk of entering a downward spiral of dyspnea, sedentariness, demotivation, and, finally, deconditioning [33] .…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the PR program improved static and dynamic lung volumes, exercise tolerance and dyspnea perception regardless of the severity of airflow limitation. Despite the many clinical trials conducted in severe patients with COPD and the contrasting results [21,23,24,25,26,27], our data support the idea that no patients, neither those with moderate disease nor the more severely hyperinflated [28], should be excluded from a PR workout. Our data are in line with recent reports that describe an increase in FEV 1 of 99 ml paralleled by a reduction in RV of 240 ml after a 3-week PR program in severe COPD patients [21], while a recent physiological study in 22 severe COPD patients by de Albuquerque et al [29] has reported important improvements in static lung volumes after 8 weeks of exercise training, although the difference was not significant.…”
Section: Discussioncontrasting
confidence: 47%
“…Predicted values for lung function variables are from Quanjer [22]. As the literature on the effect of PR on D LCO is scarce, the study was powered considering previous reports that investigated lung volume changes following PR in COPD [23]. Considering a 10% dropout rate and the need for a subgroup analysis, we set the minimum target number for the study population to be around 200 patients.…”
Section: Methodsmentioning
confidence: 99%
“…In a randomized controlled trial of a home-based 12-week training program involving 58 severe or very severe COPD patients, a significant increase could be demonstrated (p < 0.008) [10]. In another, nonrandomized observational study of 102 COPD patients who followed a 7-week program of pulmonary rehabilitation, the authors came to the conclusion that patients with worse disease status (combination of lower FEV 1 , more hyperinflation, lower exercise capacity, and worse quadriceps force) improved most in endurance exercise capacity [18]. …”
Section: Discussionmentioning
confidence: 99%